The Effectiveness of Role Play on Knowledge and Skills of Spinal Injury Indications Evacuation Improvement - Saputro, Mahmud Gunggung; Sudiro, Sudiro; Mahardini, Fina; Shobirun, Shobirun (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Spinal injuries are paralysis-causing injuries caused by trauma or disease processes. Members of the Youth Red Cross still have limited knowledge and abilities when it comes to evacuating signs of spinal cord injury. When it comes to performing first aid, knowledge and abilities are crucial. The role-playing approach is one of the methods used to improve knowledge and abilities. The research aimed to find out the effectiveness of role plays in developing knowledge and evacuation skills of spinal cord injury signs in SMAN 1 Ngemplak Youth Red Cross members. Methods: This study used a quasi-experimental design with a control group and a pretest-posttest design. Purposive sampling was employed using a sample of 40 respondents who were divided into two groups: 20 respondents in the control group and 20 respondents in the intervention group. A questionnaire and an observation sheet were utilized as part of the research instrument. On the knowledge variable, the independent t-test was utilized, and on the skill variable, the Mann-Whitney test was used. Results: Between the control and intervention groups, there were substantial differences in knowledge and skill factors. This is demonstrated by a significance value of 0.01 in the knowledge variable and a significance value of 0.023 in the skills variable. Conclusion: For Youth Red Cross SMAN 1 members, role play was effective in developing knowledge and skills of the evacuation of spinal cord injury indicators.